Implementasi Program Makan Bergizi Gratis Dalam Prespektif SDGs 8 Di Kabupaten Probolinggo (Studi pada SPPG Desa Matekan Kecamatan Besuk Kabupaten Probolinggo) - Nurul Faizzah; Veronica Sri Astuti Niwangsih; Mastina Maksin (Universitas Mbojo Bima, 2026)
This study is motivated by the implementation of the Free Nutritious Meal Program (MBG) as a government policy that not only focuses on improving nutrition but also has the potential to promote economic growth through job creation. This research aims to analyze the implementation of the MBG program from the perspective of SDGs 8 (Decent Work and Economic Growth) at SPPG Desa Matekan, Besuk District, Probolinggo Regency. This study employs a qualitative descriptive method with data collected through observation, interviews, and documentation. Data analysis is conducted using the policy implementation model of Van Meter and Van Horn, which includes policy standards and objectives, resources, inter-organizational communication, characteristics of implementing agencies, social, economic, and political conditions, and implementer disposition. The results indicate that the implementation of the MBG program has generally been well executed and has contributed to job creation, increased community income, and strengthened the role of local MSMEs. The program demonstrates a clear linkage to the achievement of SDGs 8, particularly in promoting decent work and inclusive economic growth. However, several challenges remain, including variations in implementation quality, budget efficiency, and the emergence of perceived inequality across sectors, particularly in comparison to the welfare of educators.